ИСПОЛЬЗОВАНИЕ МЕЖПРЕДМЕТНЫХ СВЯЗЕЙ КУРСА ФИЗИКИ С РАДИОЭЛЕКТРОНИКОЙ ПРИ ПОДГОТОВКЕ УЧИТЕЛЕЙ ФИЗИКИ - Ермаганбетов, К.Т.; Чиркова, Л.В. (Изд-во КарГУ., 2009)
Мақалада физика оқытушыларын дайындағанда физика мен радиоэлектроника арасындағы пəнаралық байланысты жүзеге асыру əдістері қарастырылған. Бұндай байланыстың пəн мазмұндарының ғылыми жағынан қабысуларының нəтижесі екндігіне назар аударылған. Пəнаралық байланыс түрлеріне жəне олардың өзара əсерлеріне жан-жақты талдау жасал- ған. Жоғары оқу орындарында радиоэлектроника пəнін физика құбылыстары негізінде игеру өте жеңіл жəне нəтижелі болатындығы дəлелденген. Оқыту барысында қолдануға болатын пəнаралық байланыс мысалдары келтірілген. Some methodical questions of an establishment of intersubject communications between rates of physics and radio electronics are considered by preparation of teachers of physics. Some methodical questions of an establishment of intersubject communications between rates of physics and radio electronics are considered by preparation of teachers of physics. It is underlined, that intersubject communications should be considered as reflection in educational process of interscientific communications. Forms of intersubject communications are analysed: on structure, in a direction of action, on a way of interaction of directing elements. It is shown, that that efficiency of studying of radio electronics in high school raises at observance of a principle of continuity between physics and radio electronics. Examples of an establishment of intersubject communications which can be used in educational process are resulted.
Keywords: использование межпредметных связей; курсы физики; радиоэлектроника; учитель физики